Curcumin Reduces the Motility of Salmonella enterica Serovar Typhimurium by Binding to the Flagella, Thereby Leading to Flagellar Fragility and Shedding - Marathe, Sandhya Amol (J Bacteriol, 2016)
One of the important virulence properties of the pathogen is its ability to travel to a favorable environment, cross the viscous mucus barrier (intestinal barrier for enteric pathogens), and reach the epithelia to initiate pathogenesis with the help of an appendage, like flagella. Nonetheless, flagella can act as an “Achilles heel,” revealing the pathogen's presence to the host through the stimulation of innate and adaptive immune responses. We assessed whether curcumin, a dietary polyphenol, could alter the motility of Salmonella, a foodborne pathogen. It reduced the motility of Salmonella enterica serovar Typhimurium by shortening the length of the flagellar filament (from ∼8 μm to ∼5 μm) and decreasing its density (4 or 5 flagella/bacterium instead of 8 or 9 flagella/bacterium). Upon curcumin treatment, the percentage of flagellated bacteria declined from ∼84% to 59%. However, no change was detected in the expression of the flagellin gene and protein. A fluorescence binding assay demonstrated binding of curcumin to the flagellar filament. This might make the filament fragile, breaking it into smaller fragments. Computational analysis predicted the binding of curcumin, its analogues, and its degraded products to a flagellin molecule at an interface between domains D1 and D2. Site-directed mutagenesis and a fluorescence binding assay confirmed the binding of curcumin to flagellin at residues ASN120, ASP123, ASN163, SER164, ASN173, and GLN175. IMPORTANCE This work, to our knowledge the first report of its kind, examines how curcumin targets flagellar density and affects the pathogenesis of bacteria. We found that curcumin does not affect any of the flagellar synthesis genes. Instead, it binds to the flagellum and makes it fragile. It increases the torsional stress on the flagellar filament that then breaks, leaving fewer flagella around the bacteria. Flagella, which are crucial ligands for Toll-like receptor 5, are some of the most important appendages of Salmonella. Curcumin is an important component of turmeric, which is a major spice used in Asian cooking. The loss of flagella can, in turn, change the pathogenesis of bacteria, making them more robust and fit in the host.